1987
DOI: 10.1111/j.1469-8137.1987.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

AN ANALYSIS OF THE INFLUENCE OF CLONE SIZE AND STOLON CONNECTIONS BETWEEN RAMETS ON THE GROWTH OF GLECHOMA HEDERACEA L.

Abstract: SUMMARYTwo experiments were conducted in which the influence of size of clones and the persistence of stolon connections on subsequent development were examined in Gtechoma hederacea. In the first experiment, clones were grown from either one unrooted ramet or from either one, two or three connected, rooted ramets, for 8 weeks, in either nutrient-rich or nutrient-poor sand. The survival, number of ramets and dry weight of the clones produced were dependent on the number of established ramets at the start of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…This result was opposite to our second hypothesis. Sprouting of intact clones would result in the ramet increment and the adjustment of biomass allocation to ensure normal growth and development [29], [49], in which clonal integration plays an important role in the clonal growth [21], [27], [38]. The clonal growth differences were attributed to the amount of stored resources in the previous studies for the stolon or rhizome fragment [29], [33], [50].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This result was opposite to our second hypothesis. Sprouting of intact clones would result in the ramet increment and the adjustment of biomass allocation to ensure normal growth and development [29], [49], in which clonal integration plays an important role in the clonal growth [21], [27], [38]. The clonal growth differences were attributed to the amount of stored resources in the previous studies for the stolon or rhizome fragment [29], [33], [50].…”
Section: Discussionmentioning
confidence: 98%
“…buds on the layering that are the primary shoot-producing meristematic organs [34], [35], [36], [37], [38]. The clonal growth of a size-dependent clone is common [33], [38], [39], [40], [41]. One study found that the big Glechoma hederacea clone developed a greater number of ramets under favorable conditions [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translocation of resources from older to younger ramets increases the probability of daughter ramet survival (Slade & Hutchings 1987a). Physiological integration appears to involve no costs, at least in biomass terms, to the source ramet, but confers growth benefits upon the whole clone (Slade & Hutchings 1987b).…”
Section: Habitatmentioning
confidence: 99%
“…Stolon breakage reduces the capacity of clones to spread laterally, and smaller ramets are produced. Severing the stolons between ramets resulted in ramets being established at more than twice the density seen in intact clones (Slade & Hutchings 1987a).…”
Section: Structure and Physiologymentioning
confidence: 99%